Immunogenicity and Protective Efficacy of a Polyvalent DNA Vaccine against Human Orthopoxvirus Infections Based on Smallpox Virus Genes. (21st August 2012) - Maksyutov, Rinat A.; Gavrilova, Elena V.; Kochneva, Galina V.; Shchelkunov, Sergei N.
Abstract : DNA vaccines combining plasmids carrying the variola virus genes M1R, A30L, and F8L of intracellular virion surface membrane proteins as well as A36R and B7R of the extracellular virus envelope proteins under control of Rous sarcoma virus or cytomegalovirus promoters have been constructed. These DNA vaccines induced production of a high titers of vaccinia virus-neutralizing antibodies in mice similar to those elicited by the live vaccinia virus immunization. Mice vaccinated by created DNA vaccine were completely protected against a lethal (10 LD50 ) challenge with highly pathogenic ectromelia virus. These results suggest that such vaccine should be efficient in immunization of humans against smallpox.